Inundations in the delta of the Northern Dvina River - Magritsky Dmitry; Lebedeva Serafima; Polonsky Vadim; Skripnik Elena (Journal of the Geographical Institute Jovan Cvijic, SASA, 2013)
This paper provides information about the types, factors and features of ice dam and storm surge inundations in the Northern Dvina River delta, new methods and results of their research, changing the situation with inundations for a long time-period. This article contains data on current structure and regime of the Northern Dvina delta, changes of hydrological factors in XX-XXI centuries.